2023
DOI: 10.1590/1414-462x202230040033
|View full text |Cite
|
Sign up to set email alerts
|

Acessibilidade geográfica aos serviços de reabilitação de crianças com síndrome congênita do vírus Zika

Abstract: Resumo Introdução Alterações neurológicas em crianças com síndrome congênita do vírus Zika (SCZ) repercutem em atrasos no desenvolvimento e deformidades, levando à necessidade da assistência aos serviços de reabilitação. Objetivo Analisar a acessibilidade geográfica de crianças com SCZ na Região Metropolitana do Recife (RMR) e compará-la com a otimizada (distância mais próxima entre a residência da criança e o serviço). Método Estudo descritivo, incluindo 51 crianças com SCZ que residiam na RMR. Utilizaram-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(21 reference statements)
0
2
0
1
Order By: Relevance
“…A study on the support network of caregiver mothers found their dissatisfaction with the care service closest to their home, which led them to seek care in a specialized service, despite the fact that this causes inconvenience, due to the greater distance to be covered to the aforementioned specialized service (22) . Among the reasons that motivate families to seek these services, the following stand out: parents' trust in the health professionals who work there, expectations about the quality of care provided, personal and/or social network experience and satisfaction with the service (22,23) . Therefore, it is inferred that it is necessary to expand strategies beyond public policy makers, in order to involve educational institutions in the training of professionals committed to strengthening PHC.…”
Section: Discussionmentioning
confidence: 99%
“…A study on the support network of caregiver mothers found their dissatisfaction with the care service closest to their home, which led them to seek care in a specialized service, despite the fact that this causes inconvenience, due to the greater distance to be covered to the aforementioned specialized service (22) . Among the reasons that motivate families to seek these services, the following stand out: parents' trust in the health professionals who work there, expectations about the quality of care provided, personal and/or social network experience and satisfaction with the service (22,23) . Therefore, it is inferred that it is necessary to expand strategies beyond public policy makers, in order to involve educational institutions in the training of professionals committed to strengthening PHC.…”
Section: Discussionmentioning
confidence: 99%
“…Estudo sobre a rede de suporte de mães cuidadoras, constatou a insatisfação delas com o serviço/atendimento mais próximo à sua residência, o que as levam a procurar atendimento em um serviço especializado, apesar de isto exigir esforços relacionados com o deslocamento devido a distância maior (22) . Dentre as razões que motivam as famílias em busca desses serviços, destacam-se a confiança dos pais nos profissionais de saúde que lá atuam, as expectativas sobre qualidade do cuidado prestado, a experiência pessoal e/ou da rede social e a satisfação com o atendimento (22,23) . Logo, infere-se que é preciso expandir as estratégias para além dos formuladores de políticas públicas, de modo a envolver instituições de ensino na formação de profissionais comprometidos com o fortalecimento da APS.…”
Section: Discussionunclassified
“… 8 There is early evidence that children and adolescents with CP in low- and middle-income countries have limited access to rehabilitation and education services. 9 Brazil is a country with diverse socioeconomic and cultural conditions and faces many challenges, such as access to public services and evidence-based rehabilitation.…”
Section: Introductionmentioning
confidence: 99%